Sal wood sawdust derived highly mesoporous carbon as prospective electrode material for vanadium redox flow batteries - Maharjan, Makhan (2021)
This work reports the development of a prospective electrode material for the use in vanadium redox flow batteries. The developed electrode material was a high surface area activated carbon (1857 m² g⁻¹) with a large mesoporosity (1280 m² g⁻¹) that was derived using biomass residues, Sal wood sawdust (Shorea robusta), as a feedstock. The physico-chemical and electrochemical properties of Sal wood sawdust activated carbon were extensively characterized applying cyclic voltammetry and electrochemical impedance spectroscopy. The graphite plate electrode based on Sal wood sawdust activated carbon exhibited higher electro-catalytic activity and lower charge transfer resistance towards both positive and negative redox couples than when applying pristine graphite plate electrode. Further investigations on the application of static cell at higher current densities (20–80 mA cm²) revealed higher efficiencies for the Sal wood sawdust activated carbon modified graphite plate electrode in comparison with the pristine graphite plate electrode. Thus, the Sal wood sawdust can be suitable as carbon precursor for preparation of electrodes to be utilized in practical applications, such as in vanadium redox flow batteries.